2017
DOI: 10.1038/mi.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

The signaling axis of microRNA-31/interleukin-25 regulates Th1/Th17-mediated inflammation response in colitis

Abstract: Interleukin-25 (IL-25) is an important regulatory cytokine that has a key role on mucosal immune tolerance during inflammation response. However, the molecular mechanism that regulates the colonic IL-25 expression in Crohn's disease (CD) remains unclear. In this study, IL-25 level was proved to decrease in 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis mice and IL-10 knockout (KO) spontaneous colitis mice. An inverse correlation between IL-25 and miR-31 was discovered in the colons from model mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…The gene set analyses therefore suggest that the poor prognostic value of high MIR31HG expression is partly linked to intrinsic immune modulatory signaling and/or resistance. In a recent study investigating the interplay between the colonic mucosa and immune system in colitis, it was found that intestinal epithelium miR‐31‐5p expression was strongly upregulated in colitis models induced by either IL10‐knockout or chemical treatment, and miR‐31‐5p expression was also significantly higher in inflamed compared to normal mucosa from Crohn's patients . Thus, intestinal epithelial miR‐31‐5p expression seems intrinsically linked to colonic inflammation—known to increase the risk of developing CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The gene set analyses therefore suggest that the poor prognostic value of high MIR31HG expression is partly linked to intrinsic immune modulatory signaling and/or resistance. In a recent study investigating the interplay between the colonic mucosa and immune system in colitis, it was found that intestinal epithelium miR‐31‐5p expression was strongly upregulated in colitis models induced by either IL10‐knockout or chemical treatment, and miR‐31‐5p expression was also significantly higher in inflamed compared to normal mucosa from Crohn's patients . Thus, intestinal epithelial miR‐31‐5p expression seems intrinsically linked to colonic inflammation—known to increase the risk of developing CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase test results showed that miR-31 could bind to the untranslated region of IL-25 mRNA 3′ and directly regulate the expression of IL-25. The content changes of microRNA-31 in CD rats can affect the Th1/Th17 pathway mediated by IL-12/23 in the intestinal mucosa and consequently improve or aggravate colitis [ 57 ]. If IL-25 in CD mice was cleared or the content of IL-25 in the colon was decreased, the treatment effects of miR-31 inhibitors on colitis were significantly decreased.…”
Section: Role Of Il-25 In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Indeed, downregulated miR-26a leads to increased expression of IL-17 and IL-6 [ 54 ] and affects Th17/Treg balance towards Th17 cells [ 55 ]. Additionally, miR-31 drives Th17 cell differentiation through targeting IL-25, while suppressing Treg differentiation through FOXP3 [ 56 ]. Moreover, miR-212 promotes Th17 cell differentiation likely by targeting Bcl-6 [ 57 ], while miR-223 regulates the Th17 immune response in a myeloid dendritic cell-driven manner [ 46 ].…”
Section: Discussionmentioning
confidence: 99%